2005
DOI: 10.1175/mwr2874.1
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Quasi-Stationary and Shallow Orographic Snow Clouds: Spatial Distributions of Supercooled Liquid Water and Snow Particles

Abstract: On 25 February 1999, due to a winter monsoon after a cyclonic storm, orographic snow clouds formed under conditions of weak cold advection on the western side of the central mountain range of Japan. In this study, the Ka-band Doppler radar and vehicle-mounted microwave radiometer and 2D-Grey imaging probe were used to obtain unique datasets for analyzing the spatial distributions of microphysical structures of the snow clouds at the windward slope. The liquid water path, number concentration of snow particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Another explanation for the deviations in N 0 might come from the special orographic conditions at the UFS. Kusunoki et al [2005] reported increasing snow aggregation because of stronger upwinds and turbulence in a mountainous orography. These larger particles would consequently result in lower values for N 0 and λ , i.e., a broader SSD.…”
Section: Rt Model Results For 8 February 2009mentioning
confidence: 99%
“…Another explanation for the deviations in N 0 might come from the special orographic conditions at the UFS. Kusunoki et al [2005] reported increasing snow aggregation because of stronger upwinds and turbulence in a mountainous orography. These larger particles would consequently result in lower values for N 0 and λ , i.e., a broader SSD.…”
Section: Rt Model Results For 8 February 2009mentioning
confidence: 99%
“…structure of snowflakes depend strongly on the atmospheric conditions of ice cloud evolution (e.g., Kusunoki et al 2004Kusunoki et al , 2005. Because large snowflakes tend to originate when the sticking probability of snow particles increases in a relatively warm atmosphere, the melting process is another important factor in the shape and structure of falling snowflakes (e.g., Fujiyoshi 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant cold-air outbreaks (Mitnik, 1992) gain heat and moisture over the relatively warm waters of the SOJ and Tsushima current, destabilizing the atmosphere and generating clouds and precipitation (e.g., Hozumi & Magono, 1984;Tsuchiya & Fujita, 1967). Sea-effect precipitation systems then reach the northwest Japanese coast, where they are modified by coastal, inland, and orographic effects (e.g., Campbell et al, 2018;Estoque & Ninomiya, 1976;Kawamoto et al, 1963;Kusunoki et al, 2005;Nakai & Endoh, 1995;Saito et al, 1996;Yoshihara et al, 2004).…”
Section: Introductionmentioning
confidence: 99%